EU promotion of labour standards in its neighbourhood: prospects and limitations of the EU’s transnational regulatory approach - Laszlo Bruszt; Franklin Maduko; Pal, Timea (EU promotion of labour standards in its neighbourhood: prospects and limitations of the EU’s transnational regulatory approach, 2020)
This study analyses the effectiveness of the EU’s promotion of labour standards through its trade policy with the European neighbourhood. We consider the European Neighbourhood Policy as a critical case for examining the prospects and limitations of the EU’s broader agenda to govern labour standards through international trade agreements with developing countries. Using a combination of regression analysis and comparative study in two countries (Moldova and Moroccoa), we show that the EU can induce neighboring countries to improve their labour standards, albeit with significant shortcomings. In line with our domestic capacity and political prioritization hypothesis, we find that in the absence of stronger EU commitment towards strengthening domestic state labour administration, engaging domestic labour organizations and adopting a more problem-solving approach, EU-induced improvements in labour standards remain limited to the formal level and to areas that are more compatible with other major EU policy objectives (market integration, political and human rights). In this context, improvements will extend to the implementation level only when EU transnational regulatory governance is complemented by the regulatory initiatives of labour organizations active in the developing countries.